Comparison of Escherichia coli ST131 Pulsotypes, by Epidemiologic Traits, 1967–2009 - Johnson, James R.; Nicolas-Chanoine, Marie-Hélène; DebRoy, Chitrita; Castanheira, Mariana; Robiscek, Ari; Hansen, Glen; Weissman, Scott; Urban, Carl; Platell, Joanne; Trott, Darren; Zhanel, George; Clabots, Connie; et al. (Emerging infectious diseases, 2012)
Escherichia coli sequence type 131 (ST131), an emerging disseminated public health threat, causes multidrug-resistant extraintestinal infections. Among 579 diverse E. coli ST131 isolates from 1967-2009, we compared pulsotypes (>94% similar XbaI pulsed-field gel electrophoresis profiles) by collection year, geographic origin, source, and antimicrobial drug-resistance traits. Of 170 pulsotypes, 65 had >2 isolates and accounted for 85% of isolates. Although extensively dispersed geographically, pulsotypes were significantly source specific (e.g., had little commonality between humans vs. foods and food animals). The most prevalent pulsotypes were associated with recent isolation, humans, and antimicrobial drug resistance. Predominant pulsotype 968 was associated specifically with fluoroquinolone resistance but not with extended-spectrum β-lactamase production or bla(CTX-M-15). Thus, several highly successful antimicrobial drug-resistant lineages within E. coli ST131 have recently emerged and diffused extensively among locales while maintaining a comparatively restricted host/source range. Identification of factors contributing to this behavior of ST131 could help protect public health.